The Role of Detailed Geomorphic Variability in the Vulnerability Assessment of Potential Oil Spill Events on Mixed Sand and Gravel Beaches: The Cases of Two Adriatic Sites - Grottoli, Edoardo; Ciavola, Paolo (Frontiers in Earth Science, 2019)
The role of short to medium term geomorphic variation is analysed in two Italian mixed sand and gravel beaches to better understand how it could affect the vulnerability assessment to oil spill events. The study sites, Portonovo and Sirolo, are in one of the most congested areas for oil transportation in the Adriatic Sea (Ancona port). A “snapshot” situation populated with field data collected in April 2015 is compared to a “changing” situation built with previous field datasets (topographic surveys and surface sediment samplings) available for the two beaches. According to the ESI guidelines established by the National Oceanic and Atmospheric Administration (NOAA) in 2002, both Portonovo and Sirolo can be ranked as ESI 5 or 6A in most of the cases. Sediment size resulted the most decisive factor for the ESI assessment. As consequence of the bimodal direction of storms, the high geomorphic variability on the two sites is mainly related to storm berms which lead to rapid burial processes on both beaches. In oil spill circumstances, burial is considered the most alarming factor, especially on microtidal mixed beaches that develop storm berms so high and close to the shoreline. A quantification of the maximum potential depth reachable by the oil in the beach body is therefore needed for the most dynamic beaches: this could be achieved with repeated field measurements to be performed in the period between two consecutive ESI updates (5-7 years) and the addition of an appendix in the ESI maps dealing with the geomorphic characteristics of the beach. The significance of a changing ESI rank is that the authorities in charge of responding to the oil spill could be improperly prepared for the conditions that exist at a spill site if the geomorphology has changed from when it was first given an ESI rank.